Experimental Investigation of the Concentration Dependent Maximum Storage Capacity of two Inorganic Phase Change Materials. (June 2015) - Schmit, Henri; Pfeffer, Werner; Rathgeber, Christoph; Hiebler, Stefan
Abstract: In large latent heat storages with the phase change material (PCM) being a salt hydrate, it is difficult to assure the stoichiometrically correct hydrate concentration of the salt hydrate. In this study, the influence of the composition of CaBr2  + H2 O around the congruent melting CaBr2 ·6H2 O and CaCl2  + H2 O around the semi-congruent melting CaCl2 ·6H2 O on the maximum storage capacity is investigated via differential scanning calorimetry (DSC). For a CaBr2 concentration around 0.8 wt% lower than the concentration of CaBr2 ·6H2 O, a decrease of over 17% is found for the maximum storage capacity. For a CaCl2 concentration around 0.7 wt% lower than the concentration of CaCl2 ·6H2 O, a decrease of over 11% is found for the maximum storage capacity. While reproducible results for the maximum storage capacity for samples of the same concentration of CaBr2  + H2 O are obtained via DSC, this is not the case for the CaCl2  + H2 O samples. Thus, the difficulty to measure representative enthalpy curves of non-congruent melting salt hydrates via DSC is shown.